دور الجمعيات في ظل قانون حماية المستهلك العراقي رقم(1) لسنة (2010) دراسة مقارنة - لطيف, عدنان باقي; رحيم, بةختيار صديق (Journal of Legal and Political Studies, 2013)
States strongly are providing those laws - by adopting legislations- which protect the customer. That is, by facing; negative phenomena in the markets, antitrust and commercial fraud and ensure the safety and health of the community by monitoring the markets, while indeed this protection is that responsibility which must put on everyone including the customer himself because he is that main person who the center of those laws, at the same time he can help the state in way to the rule of law, of course that will be through those associations that represent their interests and defend their rights in a legal framework as one of the institutions of civil society. However, the historical foundation of those associations were date back to the beginnings of the last century, in Iraq particularly it did not come out until after 2003, but so far it still unable to carry out its functions more effectively. From this standpoint, we chose to explore our study under the title "The Role of Associations in the Iraqi Law Consumer Protection” comparatively to both Egyptian and Moroccan laws. This study has divided into two sections, the first one explores the nature of consumer protection, and the second one is about those mechanisms which associations use it to contribute in the protection of Iraqi consumers, and that is by determine the reservoir decrease in the Consumer Protection Act Iraqi No. (1) in the year (2010) and provide appropriate solutions to address them. Finally, we become to disclose our point by concluding that the Iraqi legislature did not give a fine role for consumer protection associations to receive complaints from consumers and pursued litigation on their behalf, unlike the situation in comparative law.
Keywords: commercial fraud; Legislation; Consumer Protection; Litigation